INCIDENCE AND PROGNOSIS OF RADIAL NERVE LESION ASSOCIATED WITH HUMERAL SHAFT FRACTURE - Barawi, Omer A.; Omer, Sherwan H.; Mohammed, Ahmed H. (Journal of Sulaimani Medical College, 2017)
Background Humerus is the long bone of the arm, radial nerve which is branch from the posterior cord of the brachial plexus commonly injured by fracture shaft of humerus because of close relation to the bone during it’s course in the arm, and the average incidence of radial nerve palsy with fracture of humerus in the literature is 12%. Objective To study incidence, types and nature of radial nerve injury associated with humeral shaft fracture. Subjects and Methods This is prospective study conducted at the Sulaimani Teaching Hospital and Causality Hospital during the period of June 2009 – June 2010. The study included sixty-eight patients with fracture shaft of hummers (21 females, 47 males), with an age ranging from 6 to 75 years (mean ±SE = 40± 0.67 years). Among the 68 patients 14 of them presented with neurological deficit of radial nerve dysfunction with an age ranging from 6 to 44 years (mean ±SE = 25 ± 0.67 years) (6 female and 8 male). The entire subjects met certain inclusion and exclusion criteria. Nerve Conduction Study and needle electromyography examinations were performed for those patients with radial nerve Dysfunction. The following biochemical parameter were measured complete blood count, serum calcium, serum alkaline phosphatase also X ray examination were performed in more than one view (anterior-posterior and lateral view). Results Among 68 patients with fractured humeral shaft 14 of them presented with feature of radial nerve palsy, nerve conduction study and electromyographic result showed that 10 patients (72%) have only focal demyelinating lesion (neuropraxia), (21%) 3 patients with severe radial nerve injury (neurotmesis) and 1 patient (7%) with partial radial nerve injury (axonotmesis) with the over all prevalence of about 20.6%. Among those patients with radial nerve palsy 3 of them was presented with compound fracture and associated severe radial nerve injury (neurotmesis), the remaining 11 patients presented with closed fracture.. Conclusions The incidence of radial nerve palsy with fractureed shaft humerus was 20.6%, transection of radial nerve is associated with open fractures of the humerus, nerve palsies that are part of closed fracture nearly always recovered.
Keywords: Radial nerve; Nerve injury; Fracture; Humerus